KNOWLEDGE, ATTITUDE, AND BEHAVIOR TO PREVENT COVID-19 INFECTION IN GENERATION Y IN PONOROGO REGENCY, EAST JAVA - Ridhoni Khoirul Anam; Istiqlaliyah Muflikhati (Journal of Child, Family, and Consumer Studies, 2022)
Generation Y has the highest rate of Covid-19 contaminated cases. This is due to frequent movements and activities outside the home. This study was intended to investigate the impact of individual characteristics, knowledge, and attitudes on behaviour to prevent infection with Covid-19 in Ponorogo. The sample in this study amounted to 100 people with an age range of 20-35 years, consisting of 16 people and 84 women. The sampling technique used is voluntary sampling. The questionnaire was made in a form, and the link was distributed online. Data analysis used descriptive tests and SEM-PLS. The results of the SEM-PLS show that there is a significant effect of gender on knowledge and behaviour in preventing infection with Covid-19, as well as attitudes towards behaviour in preventing infection with Covid-19. The results show no significant differences in knowledge, attitudes, and behaviours to prevent infection with Covid-19 in urban and rural individuals. Individual women have better knowledge and behaviour to prevent infection with Covid-19 than men, and good behaviour will increase behaviour to prevent infection with Covid-19. Socialization and behaviour to prevent infection with Covid-19 must be increased, especially for men.